Quality of life in patients with neovascular age related macular degeneration (n-AMD) seen in a public hospital of Malaysia - Rituparna Ghoshal,; Sharanjeet Kaur,; Norliza Mohamad Fadzil,; Somnath Ghosh,; NorFariza Ngah,; Roslin Azni Abd Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The purpose of the present study was to assess quality of life (QOL) in n-AMD patients seen in a Malaysian public hospital and to further identify visual and demographic factors that may contribute to QOL scores of these patients. Patients with any form of n-AMD in at least one eye were recruited from hospital’s ophthalmology department. Bahasa Malaysia version of National Eye Institute Visual function questionnaire-25 (NEI-VFQ-25) was administered to all participants. Demographics, visual functions (VF) including best corrected distance visual acuity (BCDVA), contrast sensitivity (CS), near visual acuity (NVA) and reading speed (RS) were recorded. Eighty-six patients (Malay=26, Indian=23, Chinese=37) aged 52 to 85 years, diagnosed with n-AMD were chosen to participate. Their mean NEI-VFQ composite score (NEI-VFQ CS) was 66.91 ± 13.07. However, no significant difference in NEI-VFQ CS between gender, races and between the two sub groups of n-AMD were observed (p>0.05). NEI-VFQ CS showed a significant association with RS (correlation coefficient (ρ) =0.627), NVA (ρ = -.660), BCDVA (ρ = -.586), CS (ρ =.0.515). A linear model showed that a combination of BCDVA, NVA, CS is accounted for a significant 38 % variability of NEI-VFQ CS (R2 =0.382, p<0.001). In conclusion, the QOL of Malaysian n-AMD patients were found to be low. Thus, the study results indicated the need of developing necessary management strategies to address this QOL issues in n-AMD patients in Malaysia. Furthermore, the present study suggested incorporating appropriate VF such as near acuity, contrast sensitivity, reading speed in clinical settings while assessing n-AMD patients as these VF explain the patient’s perception about the impact of this disease.